Vertical option spreads + website a study of the 1.8 standard deviation inflection point - Conrick, Charles John (John Wiley & Sons, Inc., 2013)
"Make trades on vertical options spreads with the precision of a laser beamVertical Options Spreads is a combination of a bona-fide academic research-based study and a complete method to trade credit and debit spreads, along with other complex option combination trades such as iron condors and butterflies. Here, the author has accumulated five years of daily data on the ETF, SPY and provided historical evidence of actual win rates at specific multiples of entry points, both in time and price level. For example, traders will be able to use the weekly options, pick a level of risk and return desired, learn how to place the trade, and then discover the actual percent return that the trade would have yielded. This must-have resource includes the basics of option trading and contains references to many excellent works by other authors that explore more about the intricacies of option mechanics and trading. It is far more than an analysis of one specific asset, SPY, featuring a study of probability theory and how it has applied to trading over the past five years, including the highly volatile 2007 to 2009 time frame and the more "normal" 2010 to 2012 time period. The book offer a thorough understanding of how price movement, actual volatility, and implied volatility all provide a complex but workable web in which the informed trader can generate excellent returns. However, the trader must have the discipline to act within the confines of probability and the "law" of large numbers refusing to place trades based on gut feelings or hunches. Offers high-probability based trading that uses the new weekly options Contains handy interactive worksheets that allow traders to select their own risk/return with precision Includes a website with daily and weekly information on the estimate of the actual standard deviation points on the price spectrum Vertical Options Spreads offers traders a research-based guide for trading Standard & Poors 500 ETF, SPY using historic and estimated probabilities and returns that will give them an edge in the marketplace"--
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Options (Finance); Probabilities; Options (Finances); Probabilités; probability; BUSINESS & ECONOMICS; Finance